1998
DOI: 10.1097/00007632-199801150-00023
|View full text |Cite
|
Sign up to set email alerts
|

Repair of the Pars Interarticularis Defect With a Cable-Screw Construct

Abstract: The cable-screw construct uses the strongest anchors (the pedicle and the lamina) and uses compression obtained with cables to stabilize the pars interarticularis. Early results indicate that this is a safe and effective technique for this difficult problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 16 publications
1
58
0
3
Order By: Relevance
“…Excellent results have been reported with the use of this method. The technique has originally been reported by Songer et al [19]. In a series of 7 patients, union could be achieved in all their cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excellent results have been reported with the use of this method. The technique has originally been reported by Songer et al [19]. In a series of 7 patients, union could be achieved in all their cases.…”
Section: Discussionmentioning
confidence: 99%
“…The constructs have to overcome the high stresses on the pars with extension and torsion. They should also not interfere with the surface area for bone grafting [14,19].…”
Section: Discussionmentioning
confidence: 99%
“…This technique needs extensive exposure, and fixation is dependent on the transverse process, which is not very strong. This technique was further simplified by Salib [16] and Songer [18] using a pedicle screw and wire or cable system to achieve strong fixation. Van Dam [19] further modified Songer's technique by passing a cable around the spinous process instead of the sublaminar position.…”
Section: Discussionmentioning
confidence: 99%
“…Hefti [9] reported a successful outcome of 88% in patients less than 20 and 71% in patients over 20 years. The primary reason for failure of fixation in the older population is due to the presence of degenerative disc disease [18]. Buck [1] originally suggested that his technique was appropriate only in patients in whom there was lysis of less than 3 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation